Dynamic control of the directional scattering of single Mie particle by laser induced metal insulator transitions - Zhu, Yanlin (2024)
Interference between the electric and magnetic dipole-induced in Mie nanostructures has been widely demonstrated to tailor the scattering field, which was commonly used in optical nano-antennas, filters, and routers. The dynamic control of scattering fields based on dielectric nanostructures is interesting for fundamental research and important for practical applications. Here, it is shown theoretically that the amplitude of the electric and magnetic dipoles induced in a vanadium dioxide nanosphere can be manipulated by using laser-induced metal-insulator transitions, and it is experimentally demonstrated that the directional scattering can be controlled by simply varying the irradiances of the excitation laser. As a straightforward application, we demonstrate a high-performance optical modulator in the visible band with high modulation depth, fast modulation speed, and high reproducibility arising from a backscattering setup with the quasi-first Kerker condition. Our method indicates the potential applications in developing nanoscale optical antennas and optical modulation devices.